Fostering Inclusive Practices: The Relationship between In-service Teachers’ Self-efficacy and Beliefs about Inclusive Practices - Martanus Ochola Omoro; Mwajabu A. K. Possi (CV. Samuel Manurung and Co, 2024)
Teachers' self-efficacy is a crucial element in fostering inclusive practices in school and classroom settings. Teachers' confidence about their ability and motivation to promote inclusive teaching practices in their classrooms is influenced by this important variable. The purpose of this study was to determine whether there is a relationship between teachers' self-efficacy and their beliefs about inclusive practices in Tanzania's primary schools. This study involved 254 in-service primary school teachers from 18 schools in Dodoma and Mwanza. This study employed a correlational study design. Findings indicate that levels of teacher self-efficacy and beliefs about inclusive practices exhibit a positive, but weak relationship. It was found that teachers' levels of self-efficacy are related to their beliefs about the effectiveness of inclusive education in teaching pupils with disabilities in general classrooms as compared with those who do not utilize inclusive education. In light of the findings of this study, it is suggested that measures be taken to improve teachers' personal variables in order to improve their competence and confidence in using inclusive instruction, building pupils' engagement, and managing classrooms in schools.